2012
DOI: 10.1002/asia.201101038
|View full text |Cite
|
Sign up to set email alerts
|

A Diketopyrrolopyrrole‐Based Colorimetric and Fluorescent Probe for Cyanide Detection

Abstract: Red means CN: A new type of diketopyrrolopyrrole-based chromophore has been synthesized as a colorimetric and fluorescent probe for the detection of cyanide using only two reaction steps. Through the addition of cyanide to the chromophore, the fluorescence emission and color were greatly changed in a highly sensitive and selective manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 67 publications
1
28
0
Order By: Relevance
“…Jang and co-workers reported that N -Boc-substituted DPP 152 reacts with tetrabutylammonium cyanide to give the adduct 153 showing different photophysical properties ( Scheme 50 ). [ 98 ] The addition of cyanides to the carbonyl groups of DPP 152 caused an almost complete disappearance of fl uorescence and a bathochromic shift in the absorption maximum. This reaction is possible due to the presence of electron-withdrawing Boc groups on the nitrogen atoms in compound 152 .…”
Section: Reviewmentioning
confidence: 99%
“…Jang and co-workers reported that N -Boc-substituted DPP 152 reacts with tetrabutylammonium cyanide to give the adduct 153 showing different photophysical properties ( Scheme 50 ). [ 98 ] The addition of cyanides to the carbonyl groups of DPP 152 caused an almost complete disappearance of fl uorescence and a bathochromic shift in the absorption maximum. This reaction is possible due to the presence of electron-withdrawing Boc groups on the nitrogen atoms in compound 152 .…”
Section: Reviewmentioning
confidence: 99%
“…[40,41] While among the binding mechanisms for CN -, such as coordination, hydrogen-bonding interactions, and nucleophilic addition reactions, reaction-based sensors show both high selectivity and sensitivity. [32,[42][43][44] As eported, the Schiff base (-HC=N-) was used as binding site to detect CN -through a nucleophilic addition reaction. [45,46] Herein, we designed and synthesized a new Schiff base 3-[(2-hydroxybenzylidene)-amino]-1H-pyridin-2-one (HL) as a fluorescence chemosensor for multi-ions.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other methods, fluorometric and colorimetric responses based on chemical reactions have attracted much attention due to their simple operation, high selectivity, high sensitivity and low cost [18,19,20,21,22]. The sensing mechanisms of fluorometric and colorimetric chemosenors for detecting CN − have been reported over the past few years, including hydrogen bonding reactions [23,24,25,26,27], forming cyanide anion complexes [28,29], electron transfer reactions [30,31,32] and nucleophilic addition reactions [33,34,35,36,37,38,39,40]. Among them, the nucleophilic addition reactions generally have high selectivity for detecting CN − .…”
Section: Introductionmentioning
confidence: 99%